Hobi Fotografi sebagai Sarana Mengekspresikan Diri dan Mereduksi Kecemasan pada Mahasiswa: Studi Fenomenologi - Robertus Rinowo Satrio Wicaksono; Robertus Budi Sarwono (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
This study aims to describe the extent to which hobbyists perceive photography as a means of self-expression and anxiety reduction. Photography, as a form of visual art, provides a space for individuals to creatively express their emotions, thoughts, and life experiences. Through photography, individuals can convey things that are difficult to express verbally, including feelings of anxiety, stress, or confusion. The method used in this study is a qualitative method, where data is collected through in-depth interviews and Focus Group Discussions (FGDs) to explore the subjective experiences of participants in more depth. The subjects in this study were 21-year-old students who have had a photography hobby for 4 to 5 years. The number of subjects in this study was 3 people who were selected purposively based on their active involvement in photography activities. Data analysis techniques used included interview transcription, data reduction, data presentation, and drawing conclusions based on the data collected from each subject. The results show that the three subjects have many similarities in their views on the psychological benefits of photography, despite differences in their respective focuses and approaches. In general, they stated that photography helps them express themselves, process and interpret past experiences, and reduce anxiety, especially in social situations or when interacting with others. Photography is also considered to increase self-confidence, provide a sense of control over situations, and serve as a medium for self-reflection. Thus, photography is not just a hobby, but also serves as a positive coping mechanism for maintaining mental health and emotional balance.